Upaya Peningkatan Kinerja Organisasi Melalui Orientasi Keunggulan Teknik Kreatif Yang Spesifik - Endang Tjahjaningsih; Mulyo Budi Setiawan (Conference In Business, Accounting, And Management (CBAM), 2012)
This research aims to develop a new theoretical approach in solving the result of research gap between the effects of organizasional learning influence towards organizational performance and analyze the development of Orientation On The Advantage Of Specific Creative Technique. Sources of orientation on the advantage of specific creative technique derived from the concept of the specifc firms resources. The research was conducted in the area Pekalongan, Rembang, Sragen, Banjarnegara, and Solo in Central Java Province. The empirical test model used was Structural Equation Modeling (SEM) by using some software, such as: AMOS 7.0, SPSS 16.0 and Microsoft Excel version. 2007. The sample size of the study was 200 owners/ leaders/ managers of Small and Medium Scale Enterprises. The results showed that learning explorative affect positively towards advantage of new product development, innovation creativity affect positively towards advantage of product differentiation, exploitative learning affect positively towards advantage of the creative process-oriented cost. Furthermore, advantage of new product development, advantage of product differentiation, advantage of the creative process- oriented cost affect positively towards organizational performance. This study contributes to the Resources-Based Theory, and Organizational learning Theory. Organizational learning theory provides an explanation explorative learning, exploitative learning, and creativity to the realm of Resources Based Theory, which is the realm of capabilities and orientation on the advantage of specific creative technique which is a competitive advantage in an organizational performance. Limitations and implications for future research and managerial implications are also discussed in this study.Keywords: Orientation On The Advantage Of Specific Creative Technique, Organizational Learning, and Organizational Performance.